Pfarrer Dr. phil. Carl Vogl (1866-1944): Ein Grenzgänger zwischen Christentum, Anarchismus, Sozialismus und Spiritismus - Willems, Joachim (Kirchliche Zeitgeschichte, 2004)
Carl Vogl managed to combine a remarkable combination of allegiances, previously considered incompatible, namely Christian theology, socialist anarchism, pro-soviet Marxism and occult spiritualism. Closer examination of his writings shows that he was trying to integrate these various ideological position within some dogmatic framework. He was carried along by hopes of some eschatological event which would produce a society in which there would be no intermediary between this world and the powers of the „other world", and no intermediary who would block the divine revolution during which both church and state would be replaced. Instead an egalitarian 'organic' socialist society would usher in the Kingdom of God.